Keterampilan Dasar Melempar, Menangkap, Dan Memukul Bola Pada Siswa Kelas Iv SD Negeri Kebun Bunga 1 Banjarmasin - Muhammad Habibie; Ari Tri Fitrianto (Aisyah Journal Of Physical Education (AJoPE) e-ISSN : 3046-790X, 2023)
The purpose of this study was to find out how high the level of basic skills in throwing, catching, and hitting the ball in grade IV students of SD Negri 1 Kebun Bunga, Banjarmasin. Academic Year 2022/2023. The research method uses observation techniques and test techniques which are carried out practically, namely the practice of basic movement abilities with small ball games. Researchers observed children's activities in the learning process in cycles one and two. While the test results data obtained from tests conducted at the end of learning. The research procedure was carried out in accordance with the research put forward by (Widyatmoko, 2016) "The stages carried out in each research cycle include: planning stage, action stage, observing stage, and reflecting stage. These steps constitute a single action unit which is referred to as a cycle of action. The results of the research using observation techniques and practical test techniques. Get an increase in basic movement abilities. As for the increase in students' basic movement abilities with an average value of cycle I was 77.5 while the average value of cycle II was 87. The increase in the average value of cycle I to cycle II was 10.5. The benefits of this research for the general public as the development of insight into learning activities and for teachers as an alternative in the use of small ball games in physical education learning.